Hybrids of HNBR and in situ polymerizable cyclic butylene terephthalate (CBT) oligomers: properties and dry sliding behavior (eXPRESS Polymer Letters, 2008)
A peroxide curable hydrogenated nitrile rubber (HNBR) was modified by cyclic butylene terephthalate oligomer (CBT), added in 100 parts per hundred rubber (phr). CBT polymerization was expected to occur simultaneously with that of the curing of the HNBR rubber (T = 190°C, t = 25 min). Differential scanning calorimetry (DSC) indicated that only a minor part of CBT has been polymerized (pCBT) in the hybrid. Dynamic mechanical thermal analysis (DMTA) revealed that HNBR formed the continuous whereas (p)CBT the dispersed phase. Mechanical properties (hardness, tensile modulus, ultimate tensile strength and strain, tear strength) of the HNBR and HNBR/CBT were determined and collated. Tribological properties were investigated with pin(steel)-onplate(rubber) (POP), with roller(steel)-on-plate (rubber) (ROP), with oscillating steel cylinder on rubber plate (Fretting) test configurations. Coefficient of friction (COF) and specific wear rate of the HNBR-based systems were determined. It was found that the resistance to wear increases with CBT hybridization. On the other hand, COF did not change much with CBT content. The friction and wear characteristics strongly depended on the test configurations. The worn surface of the HNBR systems was inspected in scanning electron microscope (SEM) to conclude the typical wear mechanisms. SEM investigation showed that the CBT was predominantly recrystallized from its molten state under the curing conditions set. The well developed prism- and platy-like, micron-scaled CBT crystals were made responsible for the reinforcing effect observed.